Revitalization of Koek & Co Building as the Center for Automotive Modification; Hi-Tech Architecture Approach (International Journal of Architecture and Urbanism, 2021)
The growth in the number of car users continues to increase to reach 537,054 units. This increase affects the need for a place for car maintenance and modification. Unfortunately, the City of Medan does not yet have a centralized, adequate, and complete car modification place. These factors are the reason for designing the Automotive Modification Center in Medan, a place or facility that provides all kinds of modifications and standard services expected to make it easier for people to channel their hobbies without being hindered by existing facilities. The application of Hi-tech architecture in this design is applied to the circulation system and building facade. With the revitalization of the Koek & Co building to become an automotive modification center, it is hoped to educate the public about the Koek & Co building’s history. The Koek & Co building was the largest workshop building in the city of Medan in 1937 and witnessed the development of the automotive world in Indonesia, especially Medan.